Effects of 6-epi-ophiobolin A on mechanical and physiological parameters of cardiomyocytes and on the reorganization and amounts of their kv4.x ion channels - Szűts, Viktória; Ötvös, Ferenc; Bencsik, Ottó; Váró, György; Jarabin, János András; Kovács, András; Rovó, László; Kiss, József Géza; Szénási, Tibor; Véha, Antal; Szekeres, András; Vágvölgyi, Csaba; et al. (Acta Biologica Szegediensis, 2016)
Ophiobolins are important members of the family of phytotoxic metabolites, and they possess antitumor, antibacterial, antifungal activities. At the same time, the knowledge on the effect of ophiobolins on ion channels is very limited. The voltage-dependent transient outward currents (I to) are determined by kv4.2 and kv4.3 ion channels. Increasing evidence points to a role of HMGB1 and synapse-associated protein 97 (Sap97) as underlying factors related to inflammation. The Sap97 associates with kv4.x type channels in the complex and modulating their kinetic properties. Our hypothesis was that Sap97 mainly localizes in the intercalated discs of the cardiac muscle, therefore the altered expression of ion channels is presumably involved in the inhibition of normal mechanical parameters and physiological function of transient outward current (I to). Our approach was to use purified 6-epi-ophiobolin A as effective molecular tools in the investigation of ion channels on cardiomyocytes. In this work, we have investigated the mechanical factors by atomic force microscope (AFM) technique and the surface expression of kv4 ion channels on the cardiomyocytes using confocal microscopy after immunofluorescence labeling. AFM study revealed that the elasticity of the cell surface, the Young’s modulus had been moderately changed, as well as the cell volume and the heights of the cells in the presence of low concentration of 6-epi-ophiobolin A. After this treatment the Sap97 binding to kv4.3 or kv4.2 channels and distribution of their complexes are also changed in the membrane accompanied by altered physiological behavior of cardiomyocytes as compared to control. A growing number of researches using these new reductionist models of inflammation on cardiomyocytes, demonstrate a role of Sap97 in specific ion channel stability important for cardiac functions. These results suggest that Sap97 deactivation or reduction can lead (directly or indirectly) to changes in the functional cell surface expression of kv4.x channels with mechanical parameters, with biophysical and biochemical properties of cardiac I to current.